Salmo tigridis, a new species of trout from the Tigris River, Turkey (Teleostei: Salmonidae) DAVUT TURAN (Turkey), MAURICE KOTTELAT (Switzerland) & YUSUF BEKTAŞ (Turkey) - Turan, Davut; Kottelat, Maurice; Bektaş, Yusuf (Zootaxa, 2011)
Salmo tigridis, new species, from the Tigris River drainage, Turkey, is distinguished from the other species of Salmo in Turkey and adjacent basins by having a greater number of scale rows between the end of the adipose-fin base and lateral line (19–20, vs. 12–17); a greater number of scale rows between dorsal-fin origin and lateral line (32–35, vs. 23–32); and a deeper and stouter caudal peduncle (its depth 11.5–12.6 % SL, vs. 9.3–11.5, except in S. cf. macrostigma).